Penerapan Digital Government Dalam Upaya Peningkatan Pelayanan Masyarakat Melalui Aplikasi Debest di Desa Beraban, Kediri, Tabanan - Dewi, Kadek Rahayu Swari; Wismayanti, Kadek Wiwin Dwi; Yasintha, Putu Nomy (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
Community service is a performance that must be optimized by the government to get satisfaction from the community. The Beraban Village Government applies Digital Government as an innovation in improving digital media-based public services. This study uses a qualitative research type with a descriptive approach. Sources of data used are primary data and secondary data. Based on this research study, using the theory of digital government according to the OECD (Organization for Economic Co-operation and Development) which consists of six indicators, namely user-driven, government as platform, digital by design, data driven, pro-activeness and open by default. Beraban Village by overcoming challenges related to technological limitations by facilitating village employees, data-based indicators that the debest application as a container for storing data is strategic in making it easier for the village government to store and manage data. Keywords: Digital Government, Public Service, Debest